PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM - Bradley Setiyadi; Revyta Revyta; Ayunda Fadhilah (Khazanah Pendidikan, 2020)
ABSTRACTThe curriculum is the core of the education process in schools. The implementation ofthe curriculum directly influences the educational outcomes. The curriculum reallydetermines the process and results of an education system. The curriculum is adescription of the material presented in learning, is also a very important component inan education system, the curriculum is a tool to achieve educational goals and at thesame time as a guide in the implementation of teaching at all types and levels ofeducation. Curriculum development is a process that plans, produces a better tool basedon the results of an assessment of the curriculum that has been in effect, so that it canprovide good teaching and learning conditions. In other words curriculum developmentis an activity to produce a new curriculum through the steps of curriculum preparationbased on the results of the assessment conducted over a certain period of time.Curriculum principles can also be regarded as rules that animate curriculumdevelopment. This principle has the aim that the curriculum is designed or produced inaccordance with the demands of all parties, namely students, parents, community andnation. In general, curriculum experts view curriculum development activities as acontinuous process, a cycle that involves several curricula, namely components,objectives, materials, activities and evaluations. This paper uses the method oftheoretical study of the principles of curriculum development. The theories put forwardin this paper are understanding the curriculum and its developers, plus theories aboutthe sources and principles of curriculum development, learning and evaluation ofcurriculum development.Keywords: curriculum concept, curriculum development, curriculum principles